Characteristics of African easterly waves associated with tropical cyclogenesis in the Cape Verde Islands region in July-August-September of 2004-2008 - Arnault, Joël; Roux, Frank (Atmospheric Research, 2011)
International audience The most common synoptic-scale disturbances related to cyclogenesis over the tropical north Atlantic Ocean are African easterly waves (AEWs) that originated from the northern African continent. However, most of these waves do not evolve in tropical depressions, storms, or hurricanes. The reasons why only few AEWs develop and the necessary conditions for cyclogenetic evolution are still the subject of intense debate. Tropical cyclogenesis occurring near the Cape Verde Islands in the eastern tropical Atlantic is investigated here with five seasons (July-August-September of 2004-2008) of European Centre for Medium-Range Weather Forecasts analyses, Meteosat-9 images, and National Hurricane Center (National Oceanic and Atmospheric Administration, National Centers for Environmental Prediction) "best track" archives. The nine named storms that first reached tropical depression intensity east of 30°W, and two among six which developed between 30 and 40°W, during these five years evolved from intense AEW troughs, associated with low-level cyclonic circulation, weak mid-level anticyclonic Saharan flow to the east, and deep convection near the center of cyclonic vorticity. The cyclogenetic evolution of three AEW troughs, which verified these conditions but failed to develop into named storms, was probably inhibited by unusually dry environment and strong vertical wind shear. The fate of other AEW troughs, which did not satisfy the necessary conditions, is also discussed.